IMPLEMENTASI PROGRAM SEKOLAH PENCETAK WIRAUSAHA (SPW) DALAM MENINGKATKAN MINAT DAN KETERAMPILAN WIRAUSAHA SISWA SMK NEGERI 1 CIKALONGKULON - Kustamaji, Erwin; Iriantara, Yosal; Ahmad, Irfan; Yoseptry, Ricky; Ningsih, Riyani Fitria; Pawaka, Wahyu (STKIP PGRI Situbondo, 2025)
This study aims to describe and analyze the implementation of the Entrepreneurial School Program (SPW) in enhancing students' entrepreneurial interest and skills at SMKN 1 Cikalongkulon. The research employs a qualitative approach, utilizing data collection techniques such as interviews, observations, and document analysis. The research subjects include students, teachers, and the school principal.cThe findings reveal that the implementation of the SPW Program encompasses structured planning, effective organization, integrated execution with the curriculum, and continuous evaluation. The program has proven effective in increasing students' entrepreneurial interest and skills, despite challenges such as budget constraints and limited human resources. Proposed solutions include strengthening collaboration with the business sector and providing teacher training to support program sustainability. This study contributes to the development of an entrepreneurial learning model at the vocational high school level, aligning with the demands of the workforce and modern society.